Antecedentes e consequentes do risco percebido pelos usuários brasileiros da Airbnb - Francis Marcean Resende Barros (2019)
Background and purpose: sharing has been reinvented with the creation of digital platforms, giving rise to sharing economy and collaborative consumption. Thus, new businesses have emerged and impacted several segments, including hospitality. As a result, critical issues such as security and privacy have also been intensified, drawing attention to the perceived risk. In the context of sharing accommodation, the purpose of this work was to demonstrate that risk is a potential mediator between its antecedents (especially the intrinsic factors of the individuals), and its consequents (such as consumer satisfaction and behavioral intention). Objective: to propose and to test a quantitative model that has perceived risk as the focal construct. Methods: this study was divided into two stages: an exploratory qualitative and a descriptive quantitative one. The population was the Brazilian Airbnb platform users’ community. In the qualitative stage, data were collected on Twitter and analyzed using the content analysis technique in order to expand the proposed research model and to develop scales. In the quantitative stage, data were collected through a survey using the snowball sampling technique and analyzed using the structural equation modeling technique in order to test the model hypotheses. Originality/Value: relationships between (a)personality traits and personal values and (b)satisfaction and behavioral intention through perceived risk was explored, demonstrating its potential as a mediator. Results: the qualitative results added five new constructs to the model: host risk, habit, user-generated content, perceived economic value, and positive surprise. Additionally, scales were developed for the first three constructs. The results of the quantitative stage showed that extraversion, neuroticism, conscientiousness, self-determination, safety and habit impact perceived risk, while perceived risk impacts satisfaction directly and intention indirectly through satisfaction. Theoretical/methodological contributions: theoretically, the study advanced in the state of the art of perceived risk in sharing accommodation context, also proposing relationships that are not covered by previous studies. Methodologically, the collection and analysis of secondary data showed an opportunity for marketing studies, as the proposed scales were satisfactory.